The Implementation of Investment Risk Management in Sharia Capital Market - Sugianto Sugianto; Sibral Malasyi (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
The Sharia Capital Market has recently increased as an investment vehicle that complies with Islamic sharia principles. However, as with all investment forms, some risks must be managed carefully. This paper describes the context, urgency and process of investment risk management in the Sharia Capital Market. The Sharia Capital Market complies with sharia principles, including the prohibition of usury and haram business. The risks investors face include business, market, sharia, and liquidity risks. Risk management supports sharia compliance, protects investments and maintains portfolio sustainability. The risk management involves identifying, assessing, developing strategies, implementing, and monitoring risks. By understanding and implementing risk management well, investors can achieve their investment goals more successfully in the Sharia Capital Market. In the financial world, investors must pay attention to investment risks before deciding to avoid losses. The meaning of investment risk also needs to be studied and understood by investors so that investors do not feel cheated and believe in 'profits and losses' when choosing the type of business to invest in and then be able to learn from the business they are running. We will discuss the technical aspects of investment risk management below later. Apart from understanding investment risks, investment stages can also be known from the financial institution investors choose. For this reason, ask about the stages of investing before you disburse funds. One type of investment that is interesting for investors is peer-to-peer. Unlike traditional financing methods, Peer-to-peer (P2P) lending uses lending marketplace and scoring technology. This means that investment risk becomes measurable and suitable for investors. The funds that have been collected will be distributed to micro entrepreneurs and SMEs who need financing with investors who want to fund these businesses. Investors who have invested their funds using a peer-to-peer lending system will not need to worry about investment risks because later investors will get appropriate returns based on consideration of the investment risk profile.